A bibliometric analysis of programmed cell death in oral cancer literature: research patterns and emerging trends (2000–2024) - Wenli Gu (Discover Oncology)
Abstract Background Programmed cell death (PCD) plays a crucial role in oral cancer pathogenesis and treatment. However, a comprehensive bibliometric analysis of the global research landscape in this field has not been conducted. This study aims to analyze the evolution and current trends of PCD research in oral cancer from 2000 to 2024. Methods Publications were retrieved from the Web of Science Core Collection database using relevant keywords related to oral cancer and PCD. VOSviewer 1.6.20 and CiteSpace 6.1R6 software were employed to conduct bibliometric analysis, including publication trends, citation analysis, co-authorship networks, keyword co-occurrence, and research hotspots. The time span was set from January 2000 to December 2024. Results A total of 963 publications were identified and analyzed. The annual publication output showed a steady increase, with a significant growth rate after 2010, dividing the study period into three distinct phases. The most productive countries were China (58.42%), South Korea (12.27%), and Japan (10.04%), with China Medical University and Kaohsiung Medical University being the leading institutions. Research hotspots evolved from traditional apoptosis studies to emerging forms of PCD such as autophagy, ferroptosis, and pyroptosis. Keyword analysis revealed three major research clusters: basic molecular mechanisms (centered around ROS and oxidative stress), clinical aspects (including prognosis and cell proliferation), and cell death pathways. Citation burst analysis identified emerging trends in targeting multiple PCD pathways simultaneously for oral cancer therapy, with special focus on treatment resistance and survival. Conclusion This bibliometric analysis provides a comprehensive overview of global research trends in PCD and oral cancer over the past two decades. The findings highlight the shift from basic mechanistic studies focusing on apoptosis to more diverse PCD pathways and translational research. Emerging research directions include the exploration of synergistic mechanisms among multiple PCD pathways, development of AI-based personalized treatment plans, investigation of microenvironment regulation of PCD, and application of novel drug delivery systems. These trends demonstrate the field's evolution toward more integrated, personalized approaches in oral cancer treatment. This study offers valuable insights for researchers and funding agencies to identify research gaps and potential collaboration opportunities in this rapidly developing field.